Tamil Malaysiana collection: a national heritage - M., Vijayalatchumy; S., Janaki (Persatuan Pustakawan Malaysia, 2013)
The Tamil Malaysiana collection at the University of Malaya Library is a unique, comprehensive and renowned collection in the country. It has been an important source of reference for researchers since its inception in 1956, which was in line with the establishment of the Indian Studies Department. The earliest collection of this library dates back to 1882. The collection is deemed a national heritage from its historical and archival contribution. Nowhere in the country attempts has been made to capture and preserve the local scene and happenings in the Tamil language. It has been a vital source of reference for activities in the country such as story writing competition, preparation of speeches, exhibitions, scholarly writings, etc. This paper traces to the first compilation of local materials published in the Tamil language and discusses briefly the translated works from the Malay language. It also lays down the current efforts taken to sustain the local collection and future plans to reach out to the nation.